La question du secret professionnel dans l’intervention clinique auprès des délinquants adultes - Lusignan, Richard (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
The conditions and the rules of practice in clinical settings limit the client's right to confidentiality. These limits are reviewed in the case of criminologists : some limits are legal while others refer to the context, the expectations and the reticences shared by the speakers in presence.In regard to past crimes and s elf-incrimination, these questions raise fundamental issues both to the level of ethics and administration of the penal justice. Besides the latter, is there a place for moral justice in our social control system ?